2009
DOI: 10.1351/pac-rep-08-09-22
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and thermophysical properties of the reference ionic liquid: 1-Hexyl-3-methylimidazolium bis[(trifluoromethyl)sulfonyl]amide (including mixtures). Part 2. Critical evaluation and recommended property values (IUPAC Technical Report)

Abstract: This article is a product of IUPAC Project 2002-005-1-100 (Thermodynamics of ionic liquids, ionic liquid mixtures, and the development of standardized systems). Experimental results of thermodynamic, transport, and phase equilibrium studies made on a reference sample of the ionic liquid 1-hexyl-3-methylimidazolium bis[(trifluoromethyl)sulfonyl]amide are summarized, compared, and critically evaluated to provide recommended values with uncertainties for the properties measured. Properties measured included therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
102
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 113 publications
17
102
0
Order By: Relevance
“…15 26 The relative atomic masses of the 11 elements have been presented as an interval, in the latest IUPAC technical report 2009. 27 Since the values reported in the IUPAC Commission in 2007 28 are within the presented interval, we choose to use the relative atomic masses recommended by the IUPAC report 2007 in this work.…”
Section: A High-precision Heat Capacity Drop Calorimetrymentioning
confidence: 99%
“…15 26 The relative atomic masses of the 11 elements have been presented as an interval, in the latest IUPAC technical report 2009. 27 Since the values reported in the IUPAC Commission in 2007 28 are within the presented interval, we choose to use the relative atomic masses recommended by the IUPAC report 2007 in this work.…”
Section: A High-precision Heat Capacity Drop Calorimetrymentioning
confidence: 99%
“…In the meantime several kinds of liquids, like phthalates [7,21,27,28], sebacates [7,29], benzoates [21], squalane [6,9,21], perfluoropolyethers [5] and ionic liquids [30,31], have been suggested as possible candidates to be viscosity reference fluids at moderately high viscosity, as a replacement for DIDP.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of difficulties, mainly related to the experimental handling of the liquids, and the experimental procedures of the measurement techniques, have shown to be very difficult to achieve very accurate and even reproduce viscosity results of ionic liquid samples [33], due to the significant effects on viscosity caused by contaminations, mainly halides or water. It has been shown that contaminations of the order of hundreds or tens of parts per million can cause important effects on viscosity [30,31,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Mixture properties measured included gas solubility, solute activity coefficient at infinite dilution, excess volume, water solubility, and liquid-liquid equilibrium (LLE) temperatures. The critical evaluation of the data, along with recommended values including their combined expanded uncertainties, are published separately [2].…”
Section: Introductionmentioning
confidence: 99%
“…Measurements have been reported on samples other than the IUPAC sample, and those results are included in the critical evaluation [2], but are not discussed here except to comment on the suitability of the techniques.…”
Section: Introductionmentioning
confidence: 99%